Pengembangan Video Animasi Iklan Berbasis Motion Graphic untuk Meningkatkan Hasil Belajar Bahasa Indonesia di Sekolah Dasar - Uci Fitriani FITRIANI; Abdul Muktadir; Bambang Parmadie (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
This study aims to determine how the development, feasibility, teacher and student responses and the effectiveness of motion graphic-based animation video media developed at SDN 06 and 07 Bengkulu City. The method used is the Research and Development method using the ADDIE model. The research instruments used were interviews, questionnaires, knowledge learning outcomes tests in the form of multiple choice questions (Multiple Choices) given through pretest and posttest and performance assessment rubrics to measure learning outcomes in skills aspects. The results showed that the developed media met the eligibility and requirements to be used as learning media. This can be seen from the material validation of 0,91, language validation 0,82 and design validation 0.86. The teacher and student responses showed a positive response to the developed media. It is also quite effective in improving students' Indonesian learning outcomes. Seen from the learning outcomes of the knowledge aspect, the significance value at (2-tailed) is 0,000 and the N-Gain Score is 70%. Meanwhile, the learning outcomes in the skill aspect of the experimental class were higher than the control class. From these data, it appears that there are differences in learning outcomes achieved by students in the experimental and control classes. Thus, it can be concluded that motion graphic-based animation video media is quite effective in improving Indonesian language learning outcomes in advertising materials in elementary schools.